Corporate climate reporting of European banks: Are these institutions compliant with climate issues? - Tim Jan Friedrich; Patrick Velte; Inge Wulf (Business Strategy and the Environment, 2022)
This article focuses on climate disclosures from STOXX Europe 600 banks during the 2017–2020 period, comprising 152 company years. Specifically, we analyze compliance based on general and bank-specific recommendations of the Task Force on Climate-related Financial Disclosures. Although our results indicate an overall increase in climate reporting quality over time, we identify major reporting gaps, such as consideration of forward-looking information (particularly related to scenario analyses). We also stress that the bank-specific recommendations are taken into account rather insufficiently. This study stands to benefit mostly researchers, business practices, and regulatory bodies owing to the future standardization of European and global sustainability reporting frameworks.
Keywords: 330; climate change; climate report; climate-related risks; environmental policy; risk management; sustainability report